Case Report: Ketogenic Diet Is Associated With Improvements in Chronic Obstructive Pulmonary Disease - Norwitz, Nicholas G.; Winwood, Russell; Stubbs, Brianna J.; D'Agostino, Dominic P.; Barnes, Peter J. (Frontiers in Medicine, 2021)
Chronic Obstructive Pulmonary Disease (COPD) is a debilitating inflammatory respiratory condition that presents with worsening breathing difficulties and it is assumed to be progressive and incurable. As an inflammatory disease, COPD is associated with recruitment of immune cells to lung tissue and increased levels of pro-inflammatory cytokines, including TNF-α, IL-1β, IL-6, IL-8, and GM-CSF. Low-carbohydrate ketogenic diets have anti-inflammatory properties that could, in theory, improve COPD symptoms and progression. Herein, we report on a 54-year-old patient (C.A.) with COPD who adopted a ketogenic diet (70% calories from fat). Subsequently, C.A. experienced a reduction in inflammatory markers in association with a meaningful improvement in lung function. His inflammatory markers decreased into the normal range and his forced expiratory volume increased by 37.5% relative to its pre-ketogenic diet value. Future research should explore nutritional ketosis and ketogenic diets as possible therapeutic options for individuals with COPD.